2018
DOI: 10.12659/msm.906936
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin 4 Silencing Aggravates Hydrocephalus Induced by Injection of Autologous Blood in Rats

Abstract: BackgroundAquaporin 4 (AQP4), the most abundant aquaporin in the brain, is a type of bidirectional water channel controlling the brain-water balance and plays a critical role in physiologic and pathologic water balance in the brain. AQP4 was reported to be elevated in hydrocephalus; therefore, we hypothesized that AQP4 contributes to hydrocephalus. In this study, the role of AQP4 in hydrocephalus was explored.Material/MethodsThe hydrocephalus rat model was established by injection of autologous blood. On Day 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…AQP4 is abundantly expressed in astrocytic endfeet processes in direct contact with blood vessels 7‐9 . The specific highly polarized expression of AQP4 was suggested to play critical roles in maintaining cerebral water balance and BBB integrity 10‐13 . Previous studies have reported that AQP4 polarity was disturbed in various neurological diseases that cause brain edema and BBB disruption 14‐17 .…”
Section: Introductionmentioning
confidence: 99%
“…AQP4 is abundantly expressed in astrocytic endfeet processes in direct contact with blood vessels 7‐9 . The specific highly polarized expression of AQP4 was suggested to play critical roles in maintaining cerebral water balance and BBB integrity 10‐13 . Previous studies have reported that AQP4 polarity was disturbed in various neurological diseases that cause brain edema and BBB disruption 14‐17 .…”
Section: Introductionmentioning
confidence: 99%
“…Our previous results have demonstrated the presence of AQP1 and AQP4 in CSF when studying different pathologies [ 26 , 27 , 34 , 46 ]. In the present study, we quantified AQP1 and AQP4 by ELISA and Western blot.…”
Section: Discussionmentioning
confidence: 99%
“…Brain-derived extracellular vesicles (EVs) have been identified in CSF and blood in both healthy and pathophysiological conditions [ 47 ]. It has been proposed that the presence of AQPs in CSF may be due to their secretion by EVs [ 26 , 27 , 46 , 48 , 49 ]. Our group has reported the expression of AQP4 in the EVs released into the ventricular system associated with ventricular zone glial activation [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 AQP4 functions in the physiology of water movement in the brain. 16 AQP4 facilitates water accumulation in cytotoxic edema and excess water clearance in the brain in vasogenic and interstitial edema. 17 In acute hydrocephalus.…”
Section: Relationship Between Aquaporin 4 and Hydrocephalusmentioning
confidence: 99%